Bahasa Inggris Bahasa Inggris: bahasa inggris - Annisa Amalia, Sitti Nur; Wahyuni, Putri Septi; Daswan, Lestari; Nola, Indra (Management and Leadership Study Programme, 2025)
This study aims to examine: (1) the effect of product quality on purchasing decisions of Hanasui products among IAIN Kendari students, (2) the effect of price on purchasing decisions, and (3) the effect of promotional strategies on the same. The research employs purposive sampling with 100 student respondents, and the data were analyzed using multiple linear regression. The findings reveal that product quality, price, and promotion each have a significant positive effect on students' purchasing decisions regarding Hanasui products. Moreover, when considered simultaneously, all three variables exert a significant influence on purchase behavior. Keywords: Product Quality, Price, Promotion, and Purchase Decision